Type‐III Superconductivity - M. Cristina Diamantini; Carlo A. Trugenberger; Sheng‐Zong Chen; Yu‐Jung Lu; Chi‐Te Liang; Valerii M. Vinokur (Advanced Science)
Abstract Superconductivity remains one of most fascinating quantum phenomena existing on a macroscopic scale. Its rich phenomenology is usually described by the Ginzburg–Landau (GL) theory in terms of the order parameter, representing the macroscopic wave function of the superconducting condensate. The GL theory addresses one of the prime superconducting properties, screening of the electromagnetic field because it becomes massive within a superconductor, the famous Anderson–Higgs mechanism. Here the authors describe another widely‐spread type of superconductivity where the Anderson–Higgs mechanism does not work and must be replaced by the Deser–Jackiw–Templeton topological mass generation and, correspondingly, the GL effective field theory must be replaced by an effective topological gauge theory. These superconductors are inherently inhomogeneous granular superconductors, where electronic granularity is either fundamental or emerging. It is shown that the corresponding superconducting transition is a 3D generalization of the 2D Berezinskii–Kosterlitz–Thouless vortex binding–unbinding transition. The binding–unbinding of the line‐like vortices in 3D results in the Vogel‐Fulcher‐Tamman scaling of the resistance near the superconducting transition. The authors report experimental data fully confirming the VFT behavior of the resistance.